Hak Sesama Muslim Di Era Modern: Studi Komparatif Syarah Ibnu Hajar Al-Asqalani dan Imam An-Nawawi - Firman Hidayat; Hidayati (Amorti: Jurnal Studi Islam Interdisipliner, 2026)
Islam is a perfect religion that governs and addresses every aspect of life. Among the matters given special attention are the rights of fellow Muslims. To foster a close and strong Islamic brotherhood, one way to achieve this is by upholding the rights of fellow Muslims. This study aims to analyze the concept of the rights of fellow Muslims in the hadith, compare the interpretations of Ibn Hajar Al-Asqalani and Imam An-Nawawi on the hadith, and examine its relevance in modern life. This study uses a library research method with a descriptive-analytical and comparative approach. The primary sources of this study are the book Fath al-Bari by Ibn Hajar Al-Asqalani and Syarh Sahih Muslim by Imam An-Nawawi. Secondary sources include books, scientific journals, articles, and other references related to the research theme. The results show that both scholars share a similar understanding of the importance of the rights of fellow Muslims as a means of strengthening Islamic brotherhood. However, Ibn Hajar emphasizes the fiqh and historical dimensions in his commentary on the hadith, while Imam An-Nawawi emphasizes the aspects of adab, spirituality, and moral development. In the modern era, the implementation of the hadith on the rights of fellow Muslims is very relevant in building social solidarity, strengthening brotherhood, and creating a harmonious community life amidst increasing individualism.